Virus-like intranuclear inclusions in giant cell tumor of bone - Schajowicz, Fritz; Ubios, Angela M.; Santini , M. D.; Araujo, E.; Cabrini, Rómulo Luis (1985)
Fil: Ubios, Angela M. Comisión Nacional de Energía Atómica; Argentina